'As Shakespeare so Memorably Said…': Quotation, Rhetoric, and the Performance of Politics. (March 2016) - Atkins, Judi; Finlayson, Alan
This article examines the use of quotation in British political rhetoric since 1945. It argues that quotations are not only a source of authority, but a way of claiming authorisation. The article also shows how, through quotations, party leaders try to establish connections between themselves and the common cultural resources of their audience, and how they attempt to show fidelity to a tradition even as they try to redirect it. The conclusion is that rhetorical analysis exposes the symbolic, ritualised aspect of contemporary political and ideological practices, the understanding of which requires the integration of rhetorical and performance theories.